Ground-penetrating radar imaging reveals glacier's drainage network in 3D - Church, Gregory James; id_orcid:0 000-0003-0114-9950; Bauder, Andreas; id_orcid:0 000-0001-7197-7706; Grab, Melchior; id_orcid:0 000-0002-8293-4872; Maurer, Hansruedi (Copernicus, 2021)
Hydrological systems of glaciers have a direct impact on the glacier dynamics. Since the 1950s, geophysical studies have provided insights into these hydrological systems. Unfortunately, such studies were predominantly conducted using 2D acquisitions along a few profiles, thus failing to provide spatially unaliased 3D images of englacial and subglacial water pathways. The latter has likely resulted in flawed constraints for the hydrological modelling of glacier drainage networks. Here, we present 3D ground-penetrating radar (GPR) results that provide high-resolution 3D images of an alpine glacier's drainage network. Our results confirm a long-standing englacial hydrology theory stating that englacial conduits flow around glacial overdeepenings rather than directly over the overdeepening. Furthermore, these results also show exciting new opportunities for highresolution 3D GPR studies of glaciers. ISSN:1994-0416 ISSN:1994-0424